2011
DOI: 10.1007/s12032-010-9815-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment with sorafenib and sunitinib in metastatic renal cell carcinoma: clinical outcomes from a retrospective clinical study

Abstract: Sorafenib and sunitinib are inhibitors of receptor protein tyrosine kinases (TKIs) and are approved for the treatment of metastatic renal cell carcinoma (mRCC). Although the mTOR inhibitor everolimus is effective for the treatment of patients who have failed TKI therapy, it is important to consider all available treatment options before switching therapy mode of action. Herein, we report outcomes in patients with mRCC switched to sorafenib following disease progression on sunitinib treatment. The medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…This indicates that efficacy of third line everolimus after treatment with both sunitinib and sorafenib could also be expected. Because a series of retrospective analyses suggest limited cross‐resistance between consecutive TKIs [9–20], the use of sorafenib instead of everolimus as a second line treatment after the failure of first line sunitinib should not be excluded. Furthermore, because many of the above analyses have consistently shown a longer total PFS for a sorafenib–sunitinib sequence ([15–19], reviewed in [3]), first line sorafenib can be regarded as a suitable option from the viewpoint of maximizing total PFS in patients with metastatic RCC, although the final conclusion of an ongoing prospective trial comparing sunitinib‐sorafenib vs. sorafenib‐sunitinib (SWITCH study, NCT00732914 [31]) is still awaited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that efficacy of third line everolimus after treatment with both sunitinib and sorafenib could also be expected. Because a series of retrospective analyses suggest limited cross‐resistance between consecutive TKIs [9–20], the use of sorafenib instead of everolimus as a second line treatment after the failure of first line sunitinib should not be excluded. Furthermore, because many of the above analyses have consistently shown a longer total PFS for a sorafenib–sunitinib sequence ([15–19], reviewed in [3]), first line sorafenib can be regarded as a suitable option from the viewpoint of maximizing total PFS in patients with metastatic RCC, although the final conclusion of an ongoing prospective trial comparing sunitinib‐sorafenib vs. sorafenib‐sunitinib (SWITCH study, NCT00732914 [31]) is still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Another is mammalian target of rapamycin (mTOR) inhibitor, including temsirolimus [7] and everolimus [8]. Among them, several retrospective analyses consistently reported the limited cross‐resistance between two TKIs sorafenib and sunitinib ([9–20], reviewed in [1–3]), broadening the options for the order of the drugs in sequential therapy. Furthermore, going a step further than sequential therapy with different agents of similar mechanisms, Zama et al .…”
Section: Introductionmentioning
confidence: 99%
“…Wie demgegenüber unter Berücksichtigung retrospektiver Serien unter Einschluss von >700 Patienten offensichtlich wird, entfalten Sorafenib und Sunitinib auch in der Zweitlinie nach Therapieversagen gegenüber einer TKIbasierten Erstlinienbehandlung Wirksamkeit [9,10,11,12,13].…”
Section: Systemtherapie In Der Zweitlinie Sequenzund Kombinationstheunclassified
“…Because of drug–drug interactions and the cell–drug interactions, sequential treatment may be a potential way to promote therapeutic efficacy and diminish adverse reactions . Some clinical data have indicated that sequential treatment could be adopted to improve the overall survival of cancer patients with similar tolerability as single‐line treatment …”
mentioning
confidence: 99%